1997
DOI: 10.1074/jbc.272.7.4327
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin Binding Protein (BiP) Function Is Required to Protect Cells from Endoplasmic Reticulum Stress but Is Not Required for the Secretion of Selective Proteins

Abstract: BiP/GRP78 is a lumenal stress protein of the endoplasmic reticulum (ER) that interacts with polypeptide folding intermediates transiting the secretory compartment. We have studied the secretion and the stress response in Chinese hamster ovary (CHO) cells that overexpress either wild-type immunoglobulin binding protein (BiP) or a BiP deletion molecule (residues 175-201) that can bind peptides and ATP but is defective in ATP hydrolysis and concomitant peptide release. Overexpressed wild-type BiP was localized to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
199
2
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 321 publications
(213 citation statements)
references
References 82 publications
11
199
2
1
Order By: Relevance
“…It follows that by blocking or minimizing ER stress, it may be possible to attenuate the induction of lipid biosynthesis. In support of this concept, we observed that stable overexpression of GRP78/BiP, which protects cells from agents or conditions known to cause ER stress (39,40), inhibits homocysteine-induced expression of genes involved in cholesterol biosynthesis in cultured human cells.…”
Section: Figure 11supporting
confidence: 58%
See 1 more Smart Citation
“…It follows that by blocking or minimizing ER stress, it may be possible to attenuate the induction of lipid biosynthesis. In support of this concept, we observed that stable overexpression of GRP78/BiP, which protects cells from agents or conditions known to cause ER stress (39,40), inhibits homocysteine-induced expression of genes involved in cholesterol biosynthesis in cultured human cells.…”
Section: Figure 11supporting
confidence: 58%
“…Overexpression of GRP78/BiP has been reported to protect cells from ER stress (39,40). Stably transfected cells overexpressing GRP78/BiP were generated to assess whether blocking homocysteine-induced ER stress attenuated the expression of SREBP-1 and IPP isomerase.…”
Section: Induction Of Ipp Isomerase Gene Expression By Er Stressmentioning
confidence: 99%
“…Moreover, in cells with increased BiP levels, diminished secretion of factor VIII or von Willebrand factor has been observed (39,60). Importantly, selectively increased ER chaperone expression does not produce a generalized effect on anterograde protein traffic, as export is slowed only for those secretory proteins to which chaperone binding can be detected (39,61). In the present study, Tg, a protein shown to bind GRP94, exhibits similarly delayed export from cells with increased levels of GRP94.…”
Section: Stoichiometry Of Immunoprecipitable Of Tg⅐grp94mentioning
confidence: 52%
“…2,3,5,26 Cells overexpressing GRP78 are resistant to conditions associated with ER stress. 27 The subnephritogenic dosages of tunicamycin and thapsigargin used for preconditioning in this study evoked the adaptive UPR without renal pathologic or functional effects in healthy control rats and ameliorated the severity of the disease manifestations of anti-Thy1 nephritis.…”
Section: Discussionmentioning
confidence: 99%